The Performance of Secretariat DPRD to Appreciation the Implementation of function DPRD North Sulawesi Provincie. - Sahala, Jecica Nansi; Dengo, Salmin; Londa, Verry (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT   Parliament Secretariat is device area that has the task of providing administrative serv ices to   the Parliament, so that the performance of the secretariat of the council will also determine the   success of the implementation of Council functions. This research is to answer the question " how   the  performance  of  the  North  Sulawesi  Provincial  Parliament  Secretariat  in  supporting  the   implementation of the functions of Parliament.   Research  using  qualitative  methods.  In  this  case  the  performance  indicators  used  are   effectiveness  ,  efficiency  ,  responsiveness  ,  and  accountability  .  Informants  in  this  study  were   drawn  from  officials  and  employees  of  the  secretariat  of  Parliament  and  the  leadership  of  Parliament  and North Sulawesi. Collecting data with interview techniques ; while the analysis of   data using interactive model analysis techniques of Miles and Hubernann .   The  results  showed  :  (1)  the  level  of  effectiveness  is  quite  nice  views  of  the  successful   implementation of programs and activities that have been set, and the level of achievement of the   target outcomes; (2) the level of efficiency is quite good views of the  use of the budget and the   utilization of human potential employees. (3) the level of responsiveness pretty good views of the   adjustability of programs and activities adopted by the council needs, the level of capacity to deal   with the increased volume of work, and the level of ability to cope with problems or obstacles that   arise in the implementation of tasks. (4) the level of accountability pretty good views of a system of   accountability  that  do  good  to  the  chairman  of  the  board,  to  the  leadership  of  the  provincial  government, and public.    Based on the conclusions of the research results it is suggested to improve the performance   of  the  Provincial  Parliament  Secretariat  North  Sulawei   by  doing  things:  (1)  increase  the   competence   of   human   resources   through   education   and   training   of   employees   technically  functional; (2) Improve the work motivation of employees by provid ing adequate incentives ; and   (3) improving coordination among organizational units and coordination with Parliament .    Keywords : performance , functions of Parliament